Antecedente de cesárea, aborto y de cirugía tubárica como factores de riesgo de embarazo ectópico. Hospital Belén de Trujillo. 2014 - 2018 - Rebaza Toro, Hernán Eduardo (2019)
Introduction: Ectopic pregnancy (EE) is defined as the implantation of the blastocyst outside the uterine cavity. Among the risk factors that could be found for an ectopic pregnancy are the dependents to a tubal disorder, among them the antecedent of previous tubal surgery, antecedent of cesarean section, and that of abortion that cause damage and anatomical interruption of the fallopian tube. Objective: To determine the antecedent of caesarean section, abortion and tubal surgery are risk factors of ectopic pregnancy in the Belén Hospital of Trujillo during the 2014-2018 period. Method: This is an analytical, case-control study. In which the population is divided into two: with ectopic pregnancy and without ectopic pregnancy and the analysis of the frequency of exposure of each risk factor and its association. Conclusion: A history of caesarean section, abortion and tubal surgery are risk factors for ectopic pregnancy in the Belén Hospital of Trujillo.